A Two Layer Cooperative Game theoretic Approach for Optimal Operation of Fast Charging Stations. Issue 4 (2019) - Rana, Rubi; Bhattacharjee, Shayari; Mishra, Sukumar
Abstract: This paper presents a two layer energy trading framework for energy exchange among electric vehicles (EVs) and charging stations (CSs). The first layer includes peer to peer energy trading among EVs which is achieved by using assignment theoretic game model. The second layer is energy exchange among CSs which is achieved via buyer driven modified Gale Shapley model. A two layer cooperative energy trading model aims to reduce the grid dependency, power losses and ensures the optimal performance of the charging station.